75 years of the chestnut blight fungus Cryphonectria parasitica (Murr.) Barr in Europe - Radócz, László; Görcsös, Gábor; Tarcali, Gábor; Kovács, Gabriella; Ling, Qin (Acta Agraria Debreceniensis, 2014)
The chestnut blight fungus Cryphonectria parasitica is a native pathogen in East Asia and has been introduced into North America and Europe. Historical records and population genetic studies revealed at least three major introduction events from Asia into Europe. Nowadays, chestnut blight is present in almost the entire distribution range of European chestnut, i.e. from the Iberian Peninsula to the Caucasus. The C. parasitica population in most countries has been studied in respect to the diversity of vegetative compatibility (vc) types and the occurrence of hypovirulence. The vc type diversity of the different populations varied considerably. Typically, a high diversity of vc types has been found in areas with a long history of chestnut blight and where sexual recombination between divergent genotypes commonly has occurred. On the other hand, newly established populations often showed a low diversity with only one, or a few vc types present. Hypovirulence, i.e. the occurrence of C. parasitica isolates infected by Cryphonectria hypovirus 1 has been found widespread in Europe. Natural dissemination and active biological control applications have lead to a high prevalence of the hypovirus and to the recovery of many chestnut stands. Virulent cankers became hypovirus-infected within a short time and ceased expansion. There is concern that the diversity of vegetative compatibility types could increase in Europe through sexual reproduction between C. parasitica genotypes originating from different introductions. A higher level of vegetative incompatibility would not only hamper hypovirus spread within a population but could also select for lower virulence in CHV-1 and subsequently lead to an erosion of biological control. Recent studies, however, indicate that the vc type barriers are not so restrictive than previously assumed and that so far no evidence for an erosion of biological control system in high diversity populations can be observed.